2012
DOI: 10.1124/jpet.112.197590
|View full text |Cite
|
Sign up to set email alerts
|

The Autophagy-Senescence Connection in Chemotherapy: Must Tumor Cells (Self) Eat Before They Sleep?

Abstract: Exposure of MCF-7 breast tumor cells or HCT-116 colon carcinoma cells to clinically relevant concentrations of doxorubicin (Adriamycin; Farmitalia Research Laboratories, Milan, Italy) or camptothecin results in both autophagy and senescence. To determine whether autophagy is required for chemotherapyinduced senescence, reactive oxygen generation induced by Adriamycin was suppressed by N-acetyl cysteine and glutathione, and the induction of ataxia telangiectasia mutated, p53, and p21 was modulated pharmacologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
99
1
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 121 publications
(122 citation statements)
references
References 60 publications
(84 reference statements)
21
99
1
1
Order By: Relevance
“…The cellular localization could augment their respective functions and contribute to establishment of secretory phenotypes (31). On the other hands, another study reported that autophagy and senescence responses may occur independently without inexorable link, because senescence can develop when autophagy is abrogated (32). In principle, combining radiation with inhibition of the mTOR pathway might induce a distinctive autophagy type, resulting in autophagic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…The cellular localization could augment their respective functions and contribute to establishment of secretory phenotypes (31). On the other hands, another study reported that autophagy and senescence responses may occur independently without inexorable link, because senescence can develop when autophagy is abrogated (32). In principle, combining radiation with inhibition of the mTOR pathway might induce a distinctive autophagy type, resulting in autophagic cell death.…”
Section: Discussionmentioning
confidence: 99%
“…35 However, inhibition of autophagy only delays, but does not fully abrogate the senescence phenotypes. 36,37 The finding suggests that autophagy plays an accelerating role during cellular senescence. Generally, common stimuli can simultaneously induce apoptosis and autophagy in a mutually exclusive manner, which may be a result of variable thresholds for both processes or from a different cellular decision between the 2 responses, thereby linking their mutual inhibition.…”
mentioning
confidence: 88%
“…11 Some studies demonstrate that autophagy is positively correlated with senescence. 12,13 Conversely, increasing evidence reveals the negative correlation between autophagy and senescence. For example, Kang et al reported that autophagy impairment can induce premature senescence in primary human fibroblasts, 14 and Harrison et al verified that rapamycin, an MTOR inhibitor and an autophagy activator, can extend the life span of mice and be a potential anti-aging drug.…”
Section: Introductionmentioning
confidence: 99%